Common Problems Found in the Methodological Approach to Small Bowel Biopsies in the Diagnosis of Celiac Disease. Issue 3 (September 2019) - Donat, Ester; Roca, Maria; Masip, Etna; Polo, Begoña; Ramos, David; Ribes-Koninckx, Carmen
Abstract : ABSTRACT: Small bowel biopsy (SBB) is not always helpful to establish celiac disease diagnosis. Hence we have conducted a retrospective study to know the amount of SBB in our center that was not optimal for this purpose. Histological findings were not appropriate for diagnosis in 3.56% (34 out of 955). The main problem encountered was inadequate sample cutting, although this could be solved by a new recut in almost 30% of cases.